ASSESSING THE IMPACT OF MICROFINANCE SCHEMES ON WOMEN'S EMPOWERMENT IN RURAL RAJASTHAN (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This study examines the case of Rajasthan, where a predominantly rural population and deeply rooted socio-cultural norms shape the scope and effectiveness of microfinance interventions. The state's traditional socio-cultural environment, low literacy rates, and persistent gender inequality create specific challenges for microfinance initiatives, making it a critical area for research. This study explored the implementation, outcomes and challenges of microfinance initiatives on women's empowerment in rural Rajasthan. The study assesses the ways in which microfinance fosters social and economic growth for rural women, with a particular focus on the Stand-Up India Scheme, Pradhan Mantri MUDRA Yojana (PMMY), Rajasthan State Rural Livelihood Mission (RSRLM), and National Rural Livelihood Mission (NRLM). From 2020 to 2023, the study uses a secondary data-based approach to gather information from official reports, economic surveys, NABARD publications, and academic literature. The findings indicate that its impacts differ depending on the geographic area. While tribal and isolated communities still face structural and sociocultural impediments, empowerment results are more noticeable in non-tribal and economically developed districts, such as Ajmer and Bhilwara. The findings also suggest that microfinance can significantly promote gender-inclusive development, but in order to guarantee significant and long-lasting empowerment, a more comprehensive and gender-sensitive implementation strategy that includes capacity building, digital access, community engagement, and focused policy interventions is necessary.